2018
DOI: 10.1213/xaa.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Anesthesia to Facilitate Organ Blood Flow During the First Penile Transplantation in the United States: A Case Report

Abstract: Regional anesthesia has been used to help create local sympathectomy and improve blood flow in plastic surgery procedures involving tissue grafts and flaps. However, anesthetic techniques that reduce systemic vascular resistance must be used with caution in patients with aortic stenosis (AS). Combined neuraxial and general anesthesia with careful titration of the local anesthetic dose can be a safe approach for patients with AS undergoing microvascular procedures. We present the anesthetic management of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated an increase in vessel diameter and increased blood velocity through said vessels when a PNB or neuraxial block is performed. [2][3][4][5][6] Herein, we present the use of serial daily PNB to decrease postsurgical pain and increase perfusion to a compromised limb with ongoing ischemia secondary to arterial and venous thrombi in a pediatric patient after heart transplant. Written Health Insurance Portability and Accountabilty Act (HIPAA) authorization for publication of the present case was obtained from the patient's guardian, and this article adheres to the applicable Enhancing the QUAlity and Transparency of health Research (EQUATOR) guidelines.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated an increase in vessel diameter and increased blood velocity through said vessels when a PNB or neuraxial block is performed. [2][3][4][5][6] Herein, we present the use of serial daily PNB to decrease postsurgical pain and increase perfusion to a compromised limb with ongoing ischemia secondary to arterial and venous thrombi in a pediatric patient after heart transplant. Written Health Insurance Portability and Accountabilty Act (HIPAA) authorization for publication of the present case was obtained from the patient's guardian, and this article adheres to the applicable Enhancing the QUAlity and Transparency of health Research (EQUATOR) guidelines.…”
mentioning
confidence: 99%